a) \(\frac{2}{3}\sqrt {9{x^3}} + 4x\sqrt {\frac{x}{4}} - {x^2}\sqrt {\frac{1}{x}} \)
\(\begin{array}{l} = \frac{2}{3}.3\sqrt {{x^2}.x} + 4x.\frac{1}{2}\sqrt x - \sqrt {{x^4}\frac{1}{x}} \\ = 2x\sqrt x + 2x\sqrt x - \sqrt {{x^3}} \\ = 4x\sqrt x - x\sqrt x \\ = 3x\sqrt x \end{array}\)
b) \(\frac{{{a^2} - 5}}{{a + \sqrt 5 }}\) với a \( \ne - \sqrt 5 \)
\(\frac{{{a^2} - 5}}{{a + \sqrt 5 }} = \frac{{\left( {a + \sqrt 5 } \right)\left( {a - \sqrt 5 } \right)}}{{a + \sqrt 5 }} = a - \sqrt 5 \)
Đúng 0
Bình luận (0)